ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN MEMBELI OLEH KONSUMEN DI SUPERMARKET LIGO MITRA PONTIANAK - Herwita, Modesta; Okianna, Okianna; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study almed to defermine the factors which influence purchasing delisions by consumers in the supermarket Ligo Mitra Pontianak. The research method used in this study was descriptive analyzes by qualitative research. Source and research data is a consumers do the shopping process in the Supermarket Ligo Mitra Pontiana meanwhile The data is year end documents collected by The person in charge. The result showed That purchasing decisions by consumers in the Supermarket Ligo Mitra Pontianak factors such as : 1). Fixing of prices given by ligomitra which is standardized and considered capable of competing from the post until now. 2). The company’s location is very strategic and a large parking area. 3). Neatly arranged store layout easy to take so it does note make consumers go round and round. 4). Sales person are friendly and sprightly in providing information. 5).product excellence that can not be doubted and 6).promosi carried out by Supermarket and which is hild every month, durring the holiday and when company birthday. Because Supermarket Ligo Mitra considered capable of fulfilling some factors from there consumers make the decisions to buy at Supermarket Ligo Mitra Pontianak. Keywords : Purchasing Decisions, Marketing Management